The New Canada Health Transfer: Increasing Disparity and Supporting Inertia? - Tsang, Adrian; Neves, Justin (The Meducator, 2012)
The current Canada Health Transfer which distributes $27 billion in cash and $13.6 billion in tax points to the provinces to support health care, will expire in 2014. Near the end of 2011, the Harper government surprised Canadians with a take-it-or-leave-it deal, whereby the Canada Health Transfer would be delivered with no-strings-attached and a decline in the rate of increased spending starting in 2017. The proposed deal reflects a growing hands off approach to healthcare in federal politics, furthers the divide between “have” and “have-not” provinces and represents a missed policy window for implementing significant healthcare reforms.